Towards a high efficiency amplifier based on Raman amplification. (27th November 2019) - Vieux, G; Brunetti, E; Cipiccia, S; Eliasson, B; Ersfeld, B; Farmer, J P; Hur, M S; Lemos, N; Welsh, G H; Wiggins, S M; Yang, X; Yoffe, S R; et al.
Abstract: Ultra high power laser amplifier systems based on plasma may provide a pathway to reach petawatt to exawatt powers, vastly exceeding the limitations imposed by the currently low damage threshold of solid state optical elements. In theory unfocused intensities of 10 17 W cm −2 could be reached. The Raman amplification scheme has been demonstrated as a promising candidate through the observation of 10% energy transfer efficiency due to amplification of noise, which implies potentially much larger efficiencies. However, controlled amplification of a seed pulse has not hitherto exceeded an efficiency of 7%. Here we discuss several saturation mechanisms that can limit the gain, such as early pump scattering and thermal effects. We show that chirped pulse Raman amplification can mitigate these deleterious effects.